Beauty Premium: Make-Up sebagai Modal Simbolik dalam Peningkatan Pendapatan Perempuan di Dunia Kerja - Diah Nadiatul Jannah (Jurnal Ekonomi dan Riset Pembangunan, 2025)
Abstract This study examines the role of make-up as a social strategy through which women construct and negotiate the beauty premium within contemporary professional settings. Using a literature review approach, this research aims to analyze how make-up contributes to the formation of the beauty premium and to explain how it functions as symbolic capital within Bourdieu’s theoretical framework. The findings indicate that aesthetic attributes can acquire social legitimacy, serve as a basis for competency attribution, and facilitate access to professional networks, informal workplace interactions, and promotion opportunities. Make-up also emerges as a convertible form of capital that can generate economic returns, including higher income, sales performance, and client-driven compensation. Overall, this study demonstrates that make-up functions as a strategic instrument that strengthens women’s positionality within competitive labor environments, while simultaneously revealing the persistence of gendered biases in professional evaluation. The beauty premium thus illustrates how bodily aesthetics remain a key arena of symbolic negotiation that shapes women’s social and economic mobility in modern workplaces.